Modelling and analysis of the techno-economic and social impacts of an algal oil - Madugu, Fatima Usman (Cranfield University, 2015)
The economic viability for a microalgae production facility for the production of algal oil and bioproducts remains challenging and unanswered. Important aspects not investigated in assessment of the economic viability of algal oil are the social benefits, such as employment, local earnings and outputs created from such facilities. A model that is able to include both techno-economic and social benefits can help provide answers on the future of these technologies. The development of this type of model requires a combination of techno-economic and social impact theory. This thesis presents an integrated model that estimates the social (employment earnings, and output) and techno-economic impacts generated from a microalgae production facility. A process and system configuration of the algal production chain is selected first. The construction costs of the equipment are then calculated, followed by overall capital cost calculation. Then, the operating costs are estimated by multiplying the resources and energy usage rate by a unit price. Employment, earnings, and output generated from constructing and operating the facility is then calculated using output from the capital and operating cost with input – output multipliers to measure the impact of the series of effects generated by expenditure. The model as far as the author knows, is the first techno-economic model that addresses the social impact. A parametric analysis is carried out using two different methods to determine the viability of an algal oil production facility. Taking the economic costs and the operating parameters from the socio- techno-economic model, some key parameters are changed across a range of values, and their influence on the final cost of algal oil and job impact are analysed. The results shows highest cost contributor to the algal oil cost comes from capital costs. Productivity rate and lipid content have the highest impact both on the final algal oil costs, and the social impact outputs. Improvement would need to be made both in biology and system units.